First record of the genus Cranichis Sw. (Orchidaceae) for the state of Pará, Brazil - Hall, Climbiê Ferreira; Koch, Ana Kelly; Francener, Augusto; de Barros, Fábio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Cranichis is a Neotropical genus with about 53 species, five of which are known from Brazil. Cranichis muscosa is only known in Brazil from the states of Amazonas, Paraná and São Paulo. In this paper, a new record of C. muscosa is presented for the state of Pará, expanding the occurrence of the species.